AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SALAM - Nunung Hasanan (Pena Medika Jurnal Kesehatan, 2015)
Background:  One  cause  damage  to  cells-cells  in  the  body  that  can  cause  disease  are  free  radicals. Free  radicals  can  come  from  outside  the  body  or  from  the  body.  Ocsigen  free  radicals  or  reactive species (ROS) found in the body can be inhibited by antioxidants. Bay leaves are natural ingredients that  contain  antioxidants  because  it  contains  flavonoids.  The  purpose  of  this  study  is  to  look  at  the content of leaves as a natural antioxidant Method The research method by laboratory tests both quantitatively and qualitatively  Result:  Extraction  of  bay  leaves  (Syzygium  polyanthum)  by  maceration  using  70%  ethanol  as  a solvent.  Testing  Qualitative  (phytochemical  test)  showed  the  presence  of  flavonoids  in  extracts  of leaves,  and  the  quantitative  assay  with  DPPH  ethanol  extract  of  leaves  that  is  IC50  =  89  627,  the concentration of antioxidant compounds contained in the leaves have antioxidant effects greater than vitamin C to decrease characters radical.  Keywords: antioxidants, bay leaves, DPPH.